The Social skills of pre-school children in the light of some variables – Descriptive study on a Syrian sample – - Saud, Alaa Ahmad Tawfik; Abdallah, Mohammad Qassem (Journal of Educational and Psychological Sciences, 2022)
The research aims to study the social skills of children between 3-6 years, i.e. the early childhood, by identifying the level of social skills and Exploring the differences in the Social Skills according to some variables: Kindergarten Enrollment, mother's work, family size. to achieve the research goals, a tool has been applied for measuring the family climate and the social skills on a sample consists of (1476) mothers of children aged 3-6 years in Syria.Research result showed: The level of social skills among children in the study sample is above average, There are statistically significant differences in the social skills according to the kindergarten enrollment, There are statistically significant differences in the social skills according to the mother's work, no significant differences in the social skills according to the family size.
Keywords: The social skills; Early childhood